Effectiveness of Manual Therapy on Function in Neck Pain Patients: A Systematic Review and Meta-Analysis - Nashrillah Reyhana, Faizah; Wahyuni, Wahyuni (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Neck pain is a musculoskeletal disorder that occurs in the neck due to various factors such as incorrect ergonomic position when carrying out an activity. One intervention that can be carried out to improve the function of neck pain sufferers is by providing manual therapy. This study aims to determine the effectiveness of manual therapy for functional use in patients with neck pain. Subjects and Method: This was a meta-analysis study using PICO as follows, P=Patients with neck pain, I=manual therapy, C=non-manual therapy, O=functional improvement. The articles used in this research were obtained from several databases such as Google Scholar, NCBI, PubMed, Springer Link, Science Direct. The keywords used are